Impact of Specialized Inpatient IBD Care on Outcomes of IBD Hospitalizations: A Cohort Study. Issue 9 (September 2016) - Law, Cindy C. Y.; Sasidharan, Saranya; Rodrigues, Rodrigo; Nguyen, Deanna D.; Sauk, Jenny; Garber, John; Giallourakis, Cosmas; Xavier, Ramnik; Khalili, Hamed; Yajnik, Vijay; Ananthakrishnan, Ashwin N.
Abstract : Background: The management of inflammatory bowel diseases (IBDs; Crohn's disease, ulcerative colitis) is increasingly complex. Specialized care has been associated with improved ambulatory IBD outcomes. Aims: To examine if the implementation of specialized inpatient IBD care modified short-term and long-term clinical outcomes in IBD-related hospitalizations. Methods: This retrospective cohort study included IBD patients hospitalized between July 2013 and April 2015 at a single tertiary referral center where a specialized inpatient IBD care model was implemented in July 2014. In-hospital medical and surgical outcomes as well as postdischarge outcomes at 30 and 90 days were analyzed along with measures of quality of in-hospital care. Effect of specialist IBD care was examined on multivariate analysis. Results: A total of 408 IBD-related admissions were included. With implementation of specialized IBD inpatient care, we observed increased frequency of use of high-dose biologic therapy for induction (26% versus 9%, odds ratio 5.50, 95% confidence interval 1.30–23.17) and higher proportion of patients in remission at 90 days after discharge (multivariate odds ratio 1.60, 95% confidence interval 0.99–2.69). Although there was no difference in surgery by 90 days, among those who underwent surgery, early surgery defined as in-hospital or within 30 days of discharge, was more common in the study period (71%) compared with the control period (46%, multivariate odds ratio 2.73, 95% confidence interval 1.22–6.12). There was no difference in length of stay between the 2 years. Conclusions: Implementation of specialized inpatient IBD care beneficially impacted remission and facilitated early surgical treatment. Abstract : Supplemental Digital Content Is Available in the Text.Article first published online 2 August 2016.